Folylpolyglutamate Synthetase Gene Transcription is Regulated by a Multiprotein Complex that Binds the TEL-AML1 Fusion in Acute Lymphoblastic Leukemia - Leclerc, Guy J. (2010)
Acute Lymphoblastic Leukemia (ALL) non-random fusions influence clinical outcome and alter the accumulation of MTX-PGs in vivo. Analysis of primary ALL samples uncovered subtype-specific patterns of folate gene expression. Using an FPGS-luciferase reporter gene assay, we determined that E2A-PBX1 and TEL-AML1 expression decreased FPGS transcription. ChIP assays uncovered HDAC1,AML1, mSin3A, E2F, and Rb interactions with the FPGS promoter region. We demonstrate that FPGS expression is epigenetically regulated through binding of selected ALL fusions to a multiprotein complex, which also controls the cell cycle dependence of FPGS expression. This study provides insights into the pharmacogenomics of MTX in ALL subtypes.